IMPLEMENTASI PRINSIP WASIAT DALAM ISLAM (PERSPEKTIF HUKUM DI INDONESIA) - Mukhlisuddin, Teuku (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2024)
A will is a message about a good thing that will be carried out after a person dies. The testament comes from the word washa which means to convey or give a message or forgiveness. In other words, a will is property given by its owner to another person after the giver dies. The concept of a will in Islam refers to the transfer of assets to distant relatives or relatives who do not have inheritance rights as well as to other people. From this concept, a theory of legal reasoning regarding will law emerged, which then developed to include reasoning about its legal posistion. The aim of Islamic law is to realize the benefit of the people. One of the aspects that is the focus of this study is wills, namely the posistion of wills in the inheritance distribution system, the legal impact of testamentary events, and the legal posistion of Islmaic wills in the Indonesian legal system.